Single-cell spatial transcriptomics reveals pathogenic mechanism of renal fibrosis in imiquimod-induced lupus nephritis in mice - Yanan Xing; Yanru An; Tian Tian; Li Pu; Zhigang Lu; Ning Liang; Longqi Liu; Zhouchun Shang (Biochemistry and Biophysics Reports, 2025)
A deeper understanding of the cellular and molecular pathology pathways of renal fibrosis in lupus nephritis (LN) is essential for the accurate disease assessment and the development of novel therapeutic strategies. In this study, we employed advanced spatial transcriptomics technique to elucidate the underlying mechanism of renal fibrosis in mouse kidneys. By establishing single-nuclei and spatial transcriptomic maps for LN and control kidneys, we identified a significant activation and proliferation of fibroblasts predominantly in the inner stripe of outer medulla (ISOM) region and pinpointed a set of specific gene signatures associated with fibrosis. Furthermore, we discovered a class of pro-fibrotic macrophage subtype, Lyz2 macrophage, that promotes myofibroblast activation. We elucidated the intricate molecular interplay mechanisms involved in this process. Our study also delved into the glomerular region, revealed disease-induced alterations in gene expression and identified potential novel therapeutic targets.